Impacts on Signal Processing Techniques for Ground Penetrating Radar - Unal, Mehmet; Caliskan, Alper; Turk, Ahmet Serdar (IEEE, 2013)
This paper presents some important signal processing techniques for ground penetrating radar. Novel ultrawide band antennas are experimentally designed in this work. Obtained data from experimental studies are presented and used for B-scan and C-scan images.
Keywords: Ground penetrating radar; background removal; radar signal processing; ANTENNA DESIGN; Engineering